2020
DOI: 10.1093/infdis/jiaa394
|View full text |Cite
|
Sign up to set email alerts
|

Core Recommendations for Antifungal Stewardship: A Statement of the Mycoses Study Group Education and Research Consortium

Abstract: In recent years, the global public health community has increasingly recognized the importance of antimicrobial stewardship (AMS) in the fight to improve outcomes, decrease costs, and curb increases in antimicrobial resistance around the world. However, the subject of antifungal stewardship (AFS) has received less attention. While the principles of AMS guidelines likely apply to stewarding of antifungal agents, there are additional considerations unique to AFS and the complex field of fungal infections that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(154 citation statements)
references
References 208 publications
(267 reference statements)
2
152
0
Order By: Relevance
“…The majority of treatment courses were for oral candidiasis, and only 1% (7/580) of infants were treated for systemic disease with either amphotericin B deoxycholate ( n = 3) or fluconazole ( n = 4). A more targeted assessment of antifungal prophylaxis and treatment is needed to address needed stewardship in this area [66] .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of treatment courses were for oral candidiasis, and only 1% (7/580) of infants were treated for systemic disease with either amphotericin B deoxycholate ( n = 3) or fluconazole ( n = 4). A more targeted assessment of antifungal prophylaxis and treatment is needed to address needed stewardship in this area [66] .…”
Section: Discussionmentioning
confidence: 99%
“…20 Pharmacists are key members of antimicrobial stewardship (AMS) teams globally and have shown that they can lead AMS programs. 21 Despite a recent focus on AFS, 22 the role of the pharmacist in AFS has not been extensively explored. The aim of this systematic review is to summarise the available evidence on pharmacistled AFS programs in the hospital setting and to evaluate the impact of pharmacist-led AFS programs on the quality of systemic antifungal prescribing and infection management, antifungal usage and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Antifungals, like antimicrobials, require active stewardship initiatives to ensure responsible use and minimize development of resistance. The recent guidance from the Mycoses Study Group for antifungal stewardship recommend that all centers frequently managing patients with invasive fungal infection have access to timely conventional and non-culture based diagnostic methods for Candida species [ 29 ]. However, diagnostic stewardship (responsible use of the diagnostic test itself), is an important consideration especially for newer more costly non-culture-based methods such as T2Candida.…”
Section: T2candida Cost-effectiveness and Potential Role In Antifumentioning
confidence: 99%
“…In care settings with low pre-test likelihoods of candidemia, PPVs are too low to justify initiating antifungals based purely on a positive result [ 11 , 17 ]. The strong NPVs of T2Candida across a broad range of prevalence’s, one of its strengths is as a stewardship tool to aid in decisions regarding discontinuation of empiric antifungal treatment [ 17 , 29 ]. The standard T2Candida panel currently identifies the five commonly isolated Candida sp.…”
Section: T2candida: Strengths and Limitationsmentioning
confidence: 99%